Preparation method and application of membrane material suitable for low-concentration CO2 separation

By using a mixed matrix membrane of self-porous microporous polymer and metal organic framework filler in the membrane material, the problems of low concentration CO2 separation are solved, and efficient CO2 separation in humid environments are achieved.

CN119838432AActive Publication Date: 2025-04-18TIANJIN POLYTECHNIC UNIV

Patent Information

Application Number
CN202510045488.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-18
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently separate low concentration CO2, especially in humid environments, with low selectivity and insufficient flux during membrane separation.

Method used

Using a mixed matrix membrane material based on self-porous microporous polymers (PIM-1 and PIM-2) and metal organic framework (MOF) fillers, the affinity and flux of the membrane material to CO2 are improved by adjusting the composition and structure of the polymer and fillers.

Benefits of technology

It realizes efficient separation of low concentration CO2 in humid environments, improves the CO2 selectivity and flux of membrane materials, and overcomes the problems of low selectivity and insufficient flux in traditional technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838432A_ABST
    Figure CN119838432A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a membrane material suitable for low-concentration CO2 separation. According to a mixed matrix membrane prepared by the method, an MOF material with fluorine element sites is added to serve as a filler under the condition that a filler framework is kept unchanged, and PIM-1 and PIM-2 serve as polymer matrixes. The defects in the field of low-concentration CO2 membrane separation in a moisture environment are overcome, the filler rich in fluorine element sites and the polymer matrix are combined, and by exploring the polymer synthesis mode, temperature and time and by exploring the mode of adding the fluorine element sites under the condition that the metal organic framework is kept unchanged, the high-concentration CO2 membrane separation efficiency is improved. And the mixed matrix membrane suitable for low-concentration CO2 separation in a moisture environment is successfully synthesized and prepared. The MOF-based mixed matrix membrane with multiple fluorine element sites shows good CO2 permeability and ultrahigh CO2 / N2 selectivity in the field of membrane separation, and strong affinity among a polymer matrix, an MOF filler and CO2 molecules.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of gas separation membranes, and in particular to a preparation method and application of a membrane material suitable for low-concentration CO2 separation. Background Art

[0002] With the continuous development of human society and industrialization, CO2 emissions have become a major factor in global warming. The low CO2 component of 300-400 ppm in the air increases the difficulty of CO2 separation, so the efficient separation, recovery and capture of low-concentration CO2 are particularly important. At present, the main methods to reduce CO2 emissions are through CO2 capture, carbon storage and amine washing. However, these technologies are usually used to capture CO2 in flue gas, which has high energy consumption and certain environmental pollution. The gas separation membrane has the characteristics of green environmental protection, easy preparation and small footprint. At the same time, among the many academic journals that have been reported, there are very few reports on low-concentration CO2 membrane separation, and the lower concentration of CO2 affects the problem of difficult separation and lack of high selectivity and high flux during membrane separation. Therefore, it is crucial to develop a membrane material suitable for low-concentration CO2 separation.

[0003] Among many membrane materials, mixed matrix membranes (MMMs) based on metal organic frameworks (MOFs) play a vital role in the field of membrane separation, and the separation of low-concentration CO2 is even more inseparable from MOF-based mixed matrix membranes. The composition of MOF-based mixed matrix membranes consists of two major parts: polymer matrix and MOF filler. The groups with strong affinity for CO2 are built into MOF-based mixed matrix membranes, which is of great significance for the separation of low-concentration CO2.

[0004] In view of climate issues such as global warming and environmental deterioration, topics such as carbon peak and carbon neutrality have been continuously raised. Through years of exploration in the field of CO2 separation membranes, the present invention combines the separation characteristics of CO2 separation and MOF-based mixed matrix membranes to provide a membrane material, preparation method and application suitable for low-concentration CO2 separation in a humid environment. Summary of the invention

[0005] The present invention mixes two self-polymerized microporous polymers (PIM-1 and PIM-2) with strong affinity for CO2 and high flux as a blended polymer matrix of a mixed matrix membrane, and simultaneously explores and synthesizes a filler suitable for the polymer matrix. The filler is mixed into the blended polymer matrix to form a membrane material suitable for low-concentration CO2 separation. The affinity of the polymer for CO2 is changed by adjusting the amount of polymer monomers, catalysts and solvents. The particle size, pore size and affinity for CO2 of the filler are changed by adjusting the ratio between metal salts and organic ligands in the filler synthesis and the content of the regulator. Thus, the CO2 flux and CO2 selectivity in membrane separation are changed.

[0006] The technical problem to be solved by the present invention is: to synthesize and prepare a separation membrane suitable for low-concentration CO2 (CO2:N2 ratio within the range of 1:99 to 15:85). First, the problem of low selectivity of the polymer matrix itself under low-concentration CO2 is solved; by introducing F to impose the hydrophobicity of the membrane pores, the problem of instability of the membrane in a humid environment and the small number of CO2 adsorption sites is solved. Explorations are made on the synthesis method, dosage, time and operation of the polymer. Secondly, the problem of the synthesis of fillers and their application in blended polymer matrices is solved, and explorations are made on the synthesis method, dosage, time and reaction mode of fillers. Explorations are made on the application of fillers and the preparation method of mixed matrix membranes.

[0007] The technical solution adopted by the present invention is a method for preparing a membrane material suitable for low-concentration CO2 separation, and the method steps are as follows:

[0008] Step S1, synthesis of PIM-2 polymer: 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobisindane, decafluorobiphenyl and potassium carbonate are weighed in proportion to obtain reactants, and added to a round-bottom flask; then N,N-dimethylformamide solvent is added to fully dissolve the reactants; and the reactants are placed in an oil bath stirrer for heating and stirring and a protective gas is introduced; when the reaction is completed, the reactants are filtered and washed to obtain an off-white powder; then, the off-white powder is placed in a hydrochloric acid aqueous solution for stirring and washing; after overnight, the reactants are filtered and dried to obtain a polymer powder;

[0009] Step S2, synthesis of MOF filler: adding 2,5-dicarboxyfluorobenzene, zirconium chloride, formic acid and N,N-dimethylformamide into a reactor in a certain proportion, and transferring the reactor to an oven for heating; then centrifugation drying is performed to obtain MOF filler;

[0010] Step S3, preparation of membrane material: adding a certain amount of polymer powder and MOF filler into a solvent, wherein the polymer powder is PIM-1 prepared in a certain proportion and the PIM-2 polymer prepared in step S1, and stirring for 1 to 2 days based on the dispersion of the MOF filler to form a casting liquid; subjecting the casting liquid to ultrasonic treatment and dropping the casting liquid into a polytetrafluoroethylene mold to obtain a formed membrane material;

[0011] Step S4, activation of the membrane material: placing the formed membrane material in an oven at a certain temperature, activating and drying it to remove the residual solvent, and preparing a membrane material suitable for low-concentration CO2 separation.

[0012] Further, in step S1, 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobisindane and potassium carbonate are added to 10mL, N,N-dimethylformamide solvent, and then reacted for 0.5 to 1 hour in advance; decafluorobiphenyl is added dropwise at a flow rate of 0.5 to 1mmol / mL; the reaction temperature of the synthetic polymer is 90 to 100 degrees Celsius, the reaction time is 60 to 72 hours, and the color of the synthesized polymer changes. The ratio of 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobisindane, potassium carbonate and decafluorobiphenyl is 1:1:1. By controlling the reaction temperature and time, the molecular weight of the polymer is controlled, thereby achieving the effect of separating low-concentration carbon dioxide. This material has not been applied to the separation of low-concentration carbon dioxide in the industry.

[0013] Furthermore, in step S1, the protective gas is nitrogen or argon; when the reaction is finished, the powder is washed with methanol or ethanol solution and placed in a hydrochloric acid aqueous solution with a concentration of less than 5%, stirred for 12 to 24 hours, and filtered to obtain a polymer powder.

[0014] Furthermore, in step S1, the raw material ratio of 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobisindane, decafluorobiphenyl and potassium carbonate is 1:1:1, and the amount of N,N-dimethylformamide solvent added is 10 mL, which is increased or decreased according to the solubility of the raw materials.

[0015] Furthermore, in step S1, after decafluorobiphenyl is replaced with tetrafluoroterephthalonitrile, PIM-1 polymer powder can be synthesized; when synthesizing PIM-1, the reaction temperature is adjusted to 65 degrees Celsius and the reaction is carried out for 72 hours.

[0016] Further, in step S2, 2,5-dicarboxyfluorobenzene, zirconium chloride, and formic acid in a ratio of 1:1:100 are added to 30 mL of N,N-dimethylformamide solvent. The reaction temperature is 120 degrees Celsius and the reaction time is 72 hours. White powder is obtained by solvent exchange and washing.

[0017] Furthermore, in step S2, the raw material ratio of 2,5-dicarboxyfluorobenzene, zirconium chloride, and formic acid is: 1:1:100, and the amount of N,N-dimethylformamide solvent added is 30 mL, which is increased or decreased according to the solubility of the raw materials. By adding 2,5-dicarboxyfluorobenzene, a MOF filler suitable for low-concentration carbon dioxide is synthesized. In this synthesis method, a MOF filler suitable for low-concentration carbon dioxide is synthesized. It is not just a simple replacement of raw materials. The reaction time of 120 degrees Celsius and 72 hours and the proportion of formic acid added are all the results of our innovative exploration in this formula. In addition, the adsorption capacity of CO2 by the MOF filler can eventually reach 45cm 3 / g, compared with the UiO-66MOF filler with the same framework structure under the same conditions, which can only reach 40cm 3 / g CO2 adsorption capacity is increased by about 10%. This is very important for the separation of low-concentration CO2.

[0018] Furthermore, in step S2, the reaction temperature for synthesizing the MOF filler is 120 degrees Celsius and the reaction time is 72 hours; at the end of the reaction, solvent exchange is performed with N,N-dimethylformamide and methanol; then centrifugation is performed to obtain the precipitate and drying is performed to obtain a white filler powder.

[0019] Furthermore, in step S3, the mass fraction of PIM-2 to the total mass fraction of the polymer is 10 wt %. The addition of PIM-2 can effectively enhance the affinity of the membrane material to low-concentration CO2, because the addition of F element sites on the membrane material improves the low-concentration CO2 separation capacity of the membrane material.

[0020] Furthermore, in step S3, PIM-2 is added to chloroform or tetrahydrofuran solvent and stirred for 12 hours before adding PIM-1, and ultrasonic treatment is performed for 30 minutes every 1 to 2 hours during the stirring period.

[0021] Further, in step S3, after the two polymers are uniformly mixed, a certain amount of MOF filler is added, and the mixture is stirred for 1 to 2 days, and ultrasonic treatment is performed for 30 minutes every 1 to 2 hours during the stirring period. The optimal amount of MOF filler added is 25wt%. The membrane material with this amount of MOF filler has a good low-concentration CO2 separation effect.

[0022] Furthermore, in step S3, before casting the membrane material, the casting liquid should be ultrasonically treated for 30 minutes, and the ultrasonically treated casting liquid should be dropped into a circular mold of polytetrafluoroethylene, and then placed in chloroform or tetrahydrofuran vapor, volatilized at room temperature, and activated after peeling.

[0023] Furthermore, in step S3, the ratio of the amount of the mixed polymer and the filler is expressed by mass fraction; the solvent for dissolving the polymer and the filler is chloroform or tetrahydrofuran; after the casting liquid is added to the mold, it should be placed in a vapor environment of the solvent used and allowed to stand, and then peeled off after it is dried and formed. In this part, the present invention mainly explores the ratio between PIM-1 and PIM-2 to form a membrane material that is stable, not easy to break, has high mechanical strength, and has a good CO2 separation effect, thereby concluding that the polymer matrix with a 10% PIM-2 addition is optimal. After adding PIM-2, the separation effect of the membrane material on CO2 will be enhanced, which is an important indicator for the separation of low-concentration CO2. In the addition of MOF fillers, it was found that when the addition amount of MOF fillers reached 25wt%, the membrane material had good separation performance under low concentration CO2 (compared to most membrane materials and reached the 2019 Robeson upper bounds). At the same MOF filler content, the filler of 25wt% UiO-66 material had filler agglomeration, which was not conducive to the high selectivity screening of membrane materials under low concentration CO2. In summary, in the membrane material, by considering the flexibility, performance and suitable element sites of the material, PIM-2 containing multiple F sites, MOF fillers with F sites (only one MOF filler synthesized with 2,5-dicarboxyfluorobenzene in the full text) and PIM-1 polymer with good CO2 separation effect were cited. Through the exploration of the conditions in the material synthesis and the optimization of the membrane making process, the membrane material in the present invention was obtained. In addition, the disadvantage that the membrane material is not suitable for low concentration CO2 separation is overcome.

[0024] Furthermore, in step S4, the membrane material is placed in a vacuum oven at 60 degrees Celsius to activate the membrane material.

[0025] Furthermore, an application of a membrane material suitable for separation of low-concentration CO2, a method for preparing a membrane material suitable for separation of low-concentration CO2, and a membrane material suitable for separation of low-concentration CO2, wherein the ratio of CO2:N2 is within the range of 1:99 to 15:85; the membrane material can be directly used for separation of low-concentration CO2 without any post-processing; and the usage form can be folded, curled or cut as the application scenario changes.

[0026] The present invention has the following advantages: (1) A method for synthesizing a polymer with a strong affinity for CO2 was explored, and the polymer was mixed with a high CO2 flux polymer, so that the blended polymer matrix of the membrane material has the potential for low-concentration CO2 separation. (2) A filler suitable for low-concentration CO2 separation was synthesized and prepared and applied to the blended polymer matrix, making the overall membrane material suitable for low-concentration CO2 separation. (3) In the gas separation test, the membrane material showed strong separation performance at different CO2:N2 ratios, proving that the modified membrane material has strong universality. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Schematic diagram of gas separation according to the present invention.

[0028] Figure 2 It is a schematic diagram of the gas separation test process of the present invention.

[0029] Figure 3 Graphs showing separation performance of various mixed polymer matrix membranes when CO2:N2=15:85 (Note: graphs showing separation performance of low-concentration CO2 gas with added MOF filler are not shown, but the membrane performance can be judged based on the examples). DETAILED DESCRIPTION

[0030] In order to make the purpose, scheme and advantages of the present invention more clear, further explanation and description are provided in conjunction with the following specific embodiments and the accompanying drawings.

[0031] like Figure 1-Figure 3 The present invention is a method for preparing and applying a membrane material suitable for low-concentration CO2 separation. The mixed matrix membrane prepared by the method is a MOF material with fluorine element sites added as a filler while keeping the filler skeleton unchanged, and PIM-1 and PIM-2 are used as polymer matrices. The present invention overcomes the shortcomings in the field of low-concentration CO2 membrane separation in a humid environment, combines a filler rich in fluorine element sites with a polymer matrix, and successfully synthesizes and prepares a mixed matrix membrane suitable for low-concentration CO2 separation in a humid environment by exploring the polymer synthesis method, temperature and time, and by exploring the method of adding fluorine element sites while keeping the metal organic skeleton unchanged. The advantages and benefits of the present invention are that the MOF-based mixed matrix membrane with multiple fluorine element sites exhibits good CO2 permeability and ultra-high CO2 / N2 selectivity in the field of membrane separation, and a strong affinity between the polymer matrix, MOF filler and CO2 molecules.

[0032] In order to demonstrate the powerful low-concentration CO2 separation capability of this membrane material, we conducted low-concentration CO2 gas separation tests on the synthesized mixed matrix membrane and presented the results in the following examples. In the examples, the CO2 flux and selectivity test method of the membrane material for various CO2:N2 mixed gas ratios (mainly CO2:N2=1:99~15:85) is shown in the attached figure.

[0033] Example 1, Study on the Synthesis of PIM-2

[0034] (1) Change the amount and ratio of monomers

[0035] 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobisindane, decafluorobiphenyl and potassium carbonate were weighed in a ratio of 1:1:1 and added to 10-20 mL of N,N-dimethylformamide solvent.

[0036] (2) Change the reaction temperature and time

[0037] Use a magnetic stirring heating table to heat the oil bath, and control the reaction temperature between 90 and 100 degrees Celsius. Adjust the reaction time appropriately according to the reaction situation.

[0038] (3) The obtained powder is subjected to molecular weight test.

[0039] (4) The obtained powder was characterized by X-ray diffraction, Fourier transform infrared spectroscopy, etc.

[0040] Example 2, Preparation of Polymer Blends with Different PIM-2 Doping Ratios

[0041] (1) Preparation of pure PIM-1 membrane material

[0042] 137 mg of PIM-1 polymer powder and 3 mL of chloroform solvent were added to a 10 mL glass bottle and stirred for 12 hours, then placed in an ultrasonicator for ultrasonic treatment. The mixture was dripped into a polytetrafluoroethylene mold and placed in a chloroform vapor environment overnight for evaporation. The pure PIM-1 membrane material was peeled off and placed in a 60 ° C vacuum oven for activation and drying.

[0043] (2) Preparation of PIM-2 / PIM-1 blend membrane materials with different doping ratios.

[0044] The film preparation method is the same as that in (1), except that when adding the polymer powder, the polymer powder of PIM-2 is added in a certain proportion, and the formula is as follows:

[0045]

[0046] (3) The obtained membrane materials were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, specific surface area and porosity analysis, and scanning electron microscopy.

[0047] Example 3 Preparation and characterization of mixed matrix membranes with different filler doping ratios

[0048] (1) The preparation method of the filler used in this invention has been explained in the summary of the invention.

[0049] (2) The fillers were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, specific surface area and porosity analysis, and scanning electron microscopy.

[0050] (3) The prepared filler was mixed with a blended polymer matrix to prepare a MOF-based mixed matrix membrane suitable for low-concentration CO2 separation.

[0051] A certain amount of filler was weighed and dispersed in chloroform solvent, and then placed in an ultrasonic instrument to fully disperse it into a uniform suspension, and the polymer blend in Example 2 (2) was added. The remaining operations were the same as the membrane preparation method in Example 2 (1).

[0052] The calculation formula for the amount of filler added is as follows:

[0053]

[0054] Example 4: Testing the prepared membrane material for low-concentration CO2 gas separation

[0055] In the test, we used three gases, CO2, N2, and He, a gas flow meter, a gas mixing box, a self-made metal membrane cell, a gas chromatograph, and a connected computer. Figure 2 (shown)

[0056] In the test, the CO2:N2 ratio is set to 1:99-15:85, the test temperature is 25 degrees Celsius, the test transmembrane pressure is 1 bar, the test relative humidity is 10-85%, and the He purge gas usually determines the gas flow rate depending on the flow rate of the mixed gas. The actual test values ​​are as follows:

[0057]

[0058] The membrane material obtained in Example 2 was subjected to a low concentration CO2 (CO2:N2=15:85) gas separation test (as shown in FIG. Figure 3 The specific results are shown in the following table:

[0059]

[0060]

[0061] From the test results, we can see that as the amount of PIM-2 added increases, the permeability of CO2 decreases, but its CO2 / N2 selectivity increases, which is beneficial to our low-concentration CO2 gas separation. Combined with the mechanical strength of the membrane material obtained in Example 2, the membrane material with a 10% PIM-2 addition amount was selected as the blended polymer matrix to prepare the mixed matrix membrane.

[0062] The membrane material obtained in Example 3 was subjected to a low concentration CO2 (CO2:N2=15:85) gas separation test, and the specific results are shown in the following table:

[0063]

[0064] From the test results, we can see that with the increase of filler addition, the permeability of CO2 has a significant increase, which is due to the large number of gas transmission channels in the filler, which is conducive to the transport of low-concentration CO2. At the same time, the addition of a large number of fluorine sites is also an important factor in separating low-concentration CO2. Combined with the actual data parameters, when the filler addition amount increases to 30%, the CO2 / N2 selectivity decreases significantly. This is because the filler particles inside the membrane material have agglomerated, resulting in non-selective defects.

[0065] The membrane material in Example 3 was tested at a relative humidity of 10-85%. The test method and test environment were the same as those for other membrane materials, except that a moisture bottle and a safety bottle were added at the mixed gas inlet. The specific results are shown in the following table:

[0066]

[0067] The membrane material in Example 3 was tested at a CO2 concentration of 1-15% and good gas separation performance was also obtained. The test method and test environment were the same as those for other membrane materials and will not be elaborated here.

[0068] In summary, the present invention discloses a membrane material, preparation method and application suitable for low-concentration CO2 separation, which adopts a method of multi-fluorine element sites and a blended polymer matrix. While slightly changing the overall mechanical strength of the membrane material and not changing the separation performance, the PIM-2 polymer matrix is ​​introduced into the synthetic preparation to enhance the affinity of the membrane material for low-concentration CO2. At the same time, without changing the MOF filler skeleton, the introduction of fluorine atoms increases the hydrophobicity of the MOF filler and its binding force to CO2 molecules, thereby improving the overall low-concentration CO2 separation ability of the membrane material in a humid environment.

Claims

1. A method for preparing a membrane material suitable for low-concentration CO2 separation, characterized in that: The steps are as follows: Step S1, synthesis of PIM-2 polymer: 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobisindane, decafluorobiphenyl and potassium carbonate are weighed in proportion to obtain reactants, and added to a round-bottom flask; then N,N-dimethylformamide solvent is added to fully dissolve the reactants; and the reactants are placed in an oil bath stirrer for heating and stirring and a protective gas is introduced; when the reaction is completed, the reactants are filtered and washed to obtain an off-white powder; then, the off-white powder is placed in a hydrochloric acid aqueous solution for stirring and washing; after overnight, the reactants are filtered and dried to obtain a polymer powder; Step S2, synthesis of MOF filler: adding 2,5-dicarboxyfluorobenzene, zirconium chloride, formic acid and N,N-dimethylformamide into a reactor in a certain proportion, and transferring the reactor to an oven for heating; then centrifugation drying is performed to obtain MOF filler; Step S3, preparation of membrane material: adding a certain amount of polymer powder and MOF filler into a solvent, wherein the polymer powder is PIM-1 prepared in a certain proportion and the PIM-2 polymer prepared in step S1, and stirring for 1 to 2 days based on the dispersion of the MOF filler to form a casting liquid; subjecting the casting liquid to ultrasonic treatment and dropping the casting liquid into a polytetrafluoroethylene mold to obtain a formed membrane material; Step S4, activation of the membrane material: placing the formed membrane material in an oven at a certain temperature, activating and drying it to remove the residual solvent, and preparing a membrane material suitable for low-concentration CO2 separation.

2. The method for preparing a membrane material suitable for low-concentration CO2 separation according to claim 1, characterized in that: In step S1, 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobisindane and potassium carbonate are added to 10 mL of N,N-dimethylformamide solvent and pre-reacted for 0.5 to 1 hour; decafluorobiphenyl is added dropwise at a flow rate of 0.5 to 1 mmol / mL; the reaction temperature for synthesizing the polymer is 90 to 100 degrees Celsius, the reaction time is 60 to 72 hours, and the reaction is regulated according to the color change of the synthesized polymer.

3. The method for preparing a membrane material suitable for low-concentration CO2 separation according to claim 1, characterized in that: In step S1, the protective gas is nitrogen or argon; when the reaction is finished, the powder is washed with methanol or ethanol solution and placed in a hydrochloric acid aqueous solution with a concentration of less than 5%, stirred for 12 to 24 hours, and filtered to obtain a polymer powder.

4. The method for preparing a membrane material suitable for low-concentration CO2 separation according to claim 1, characterized in that: In step S2, 2,5-dicarboxyfluorobenzene, zirconium chloride, and formic acid in a ratio of 1:1:100 are added to 30 mL of N,N-dimethylformamide solvent. The reaction temperature is 120 degrees Celsius and the reaction time is 72 hours. White powder is obtained by solvent exchange and washing.

5. The method for preparing a membrane material suitable for low-concentration CO2 separation according to claim 1, characterized in that: In step S3, the mass fraction of PIM-2 to the total mass fraction of the polymer is: 10 wt %.

6. The method for preparing a membrane material suitable for low-concentration CO2 separation according to claim 1, characterized in that: In step S3, PIM-2 is added to chloroform or tetrahydrofuran solvent and stirred for 12 hours before adding PIM-1, and ultrasonic treatment is performed for 30 minutes every 1 to 2 hours during the stirring period.

7. The method for preparing a membrane material suitable for low-concentration CO2 separation according to claim 1, characterized in that: In step S3, after the two polymers are uniformly mixed, a certain amount of MOF filler is added and stirred for 1 to 2 days, and ultrasonic treatment is performed for 30 minutes every 1 to 2 hours during the stirring period. The optimal addition amount of MOF filler is: 25wt%.

8. The method for preparing a membrane material suitable for low-concentration CO2 separation according to claim 1, characterized in that: In step S3, before casting the membrane material, the casting liquid should be ultrasonically treated for 30 minutes, and the ultrasonically treated casting liquid is dropped into a circular mold of polytetrafluoroethylene, and placed in chloroform or tetrahydrofuran vapor, volatilized at room temperature, and activated after peeling.

9. The method for preparing a membrane material suitable for low-concentration CO2 separation according to claim 1, characterized in that: In step S4, the membrane material is placed in a vacuum oven at 60 degrees Celsius to activate the membrane material.

10. An application of a membrane material suitable for low-concentration CO2 separation, referring to the method for preparing a membrane material suitable for low-concentration CO2 separation as claimed in claim 1, characterized in that: The prepared membrane material is suitable for low-concentration CO2 separation. The membrane material is suitable for low-concentration CO2 separation, that is, the CO2:N2 ratio is within the range of 1:99 to 15:85; it is directly used in the separation of low-concentration CO2 without any post-treatment; The usage form can be folded, curled or cut according to the application scenario.

Citation Information

Patent Citations

  • Cross-linkable intrinsically-porous polymer gas separation membrane and preparation method thereof

    CN105413412A

  • Mixed matrix membrane, preparation method and application thereof

    CN113828170A

  • Preparation method of MOF-based mixed matrix gas separation membrane with stable wet environment

    CN115646220A

  • Hybrid membranes and methods of making and use thereof

    US20200325295A1

  • Membranes of glassy polymer blends with peg-crosslinked intrinsic microporous polymers for gas separations

    US20230133081A1

Cited By

  • PFA-IL-coated UiO-PIM-1-DFBP mixed matrix membrane as well as preparation method and CO2 separation application thereof

    CN121695698A

  • PFA-IL@UiO-PIM-1-DFBP hybrid matrix membrane, preparation method thereof and CO2 separation application

    CN121695698B